Old stock, new bonds? Taste, tradition, technology and the changing geographies of livestock breeds in Australia - Birdsall-Jones, Christina; Jones, Roy (Food and Agricultural Organisation and International Geographical Union, 2005)
There has been renewed geographical interest in the relationships between animals, locality and society, leading to a reappraisal of animals within capitalist agricultural systems. Farming is conceptualised as a network that is constructed between people, animals, environments and technologies in particular localities. Australian farming is a complex hybrid of ‘colonial’, ‘indigenous’ and ‘post-colonial’ discourses of society, economy and environment. Livestock have become the ‘quintessential hybrids’ in these networks, having their lives de-animalised by human intervention yet, simultaneously, being valued for their ‘commodified naturalness’.This paper examines the role of livestock in the histories and geographies of farming in Australia. Three key ‘regimes’ are identified: The ‘Colonial Period’. Prior to colonisation, no animals were kept as domestic livestock, leading to the importation of animals from Britain and conflicts between ‘colonial’ and ‘indigenous’ knowledges of the environment. The ‘Productivist’ Regime. Exposure to other economic regimes challenged UK-orientated farming practices. Animals were imported from elsewhere, significantly diversifying Australia’s national herd. The first ‘Australian’ livestock, animals recognised as new, distinct breeds, bred specifically for Australian economic and environmental conditions, were developed. This was facilitated by technological developments, including the ready transport of semen, as well as live animals, across the planet. Changing market demands also drove these changes. The current ‘Multifunctional’ Regime. The diversification of rural and agricultural activities, including emphases on hobby farming and quality foods, led to the revival of some breeds, the import of others and renewed interest in Australian animals. The Australian Rare Breeds Trust has fostered a growing interest in the heritage, national identity and conservation of livestock found in Australia. The cultivation of emus and crocodiles; the hunting and gathering of ‘bush tucker’; and the presence of feral species serve to underline the multifunctional nature of Australian food and farming, and raise questions about the ‘natural’, indigenous and domestic status of animals in Australia.This paper places particular emphasis on the import and development of breeds. It reports our findings on the historical geography of Australian, and particularly Western Australian, cattle breeds. Sources will include the records of the state Agricultural Society, to provide quantitative data on the changing fortunes of the various breeds throughout the twentieth century. Surveys and interviews with breeders who have ‘pioneered’ the introduction of new cattle types will provide more qualitative material on the motivations behind and the challenges involved in establishing new breeds in a new land.